The Impact of Adolescents’ Attachment to Peers and Parents on Aggressive and Prosocial Behavior: A Short-Term Longitudinal Study - Vagos, Paula; Carvalhais, Lénia (Frontiers in Psychology, 2020)
This short-longitudinal study analyzed the cross-sectional and longitudinal pathways linking adolescent’s quality of attachment to parents and peers and their practice of aggressive and prosocial behavior; it also explored the moderation effect of gender on those pathways. A total of 375 secondary school students (203 girls and 172 boys), aged between 15 and 19 years old, completed the Inventory of Parent and Peer Attachment and the Peer Experience Questionnaire - Revised twice, within a four-month gap. Using a path analyses approach, results showed that aggression and prosocial behavior were the strongest predictors of themselves overtime. Attachment to mother had a cross-sectional effect on aggression and on prosocial behavior via attachment to peers, and attachment to peers predicted prosocial behavior; overall, the higher the quality of attachment, the lowest the practice of aggression and the highest the practice of prosocial behavior. These effects held stable for boys and girls, though gender-based differences were found in mean levels of attachment to peers and social behaviors. Even if other variables may be in place when understanding adolescents’ social behaviors, attachment to mother and peers also seem to play a relevant role in trying to achieve safer and more positive school climates. Suggestions on how to accomplish this are shortly discussed.